The Relationships Between Talent Management Practices, Perceived Organizational Support, Employee Engagement And Employee Retention In Malaysian Glcs - Isa, Aerni (2020)
The implementation of talent management practices is highly important for Malaysian government-linked companies (GLCs) to achieve success, gain competitive advantages and successfully retain the talents in the organization. These can be achieved by providing ample support and creating positive outcome on the engagement of employees at the workplace. This study provides better understandings for practitioners and academicians on the concept of talent management practices, perceived organizational support, employee engagement and employee retention. Supported by appropriate resource-based views and self-determination theories, this study utilized a research model examining the dimensions of talent management practices i.e. talent identification, talent development and talent culture as the predictors of employee retention and employee engagement, with mediating variables of perceived organizational support and employee engagement. The study used non-probability purposive sampling technique and the target population was the employees categorized under talent pool from 47 GLCs listed in Bursa Malaysia. A total of 164 survey questionnaires were successfully collected for the study. Partial Least Squares - Structural Equation Modeling (PLS-SEM) software was utilized to test the research model and analyze the data. This study proposed and analyzed a research framework that integrates all dimensions of variables.